Plant drought stress tolerance: understanding its physiological, biochemical and molecular mechanisms. Issue 1 (1st January 2021) - Bashir, Sheikh Shanawaz; Hussain, Anjuman; Hussain, Sofi Javed; Wani, Owais Ali; Zahid Nabi, Sheikh; Dar, Niyaz A.; Baloch, Faheem Shehzad; Mansoor, Sheikh
Abstract: Plants are vulnerable to many environmental constraints which include drought, salinity, extreme temperatures, heavy metals, etc., thereby posing damage to the development and yield of major crops. Of these stresses, drought represents a severe environmental threat to plant productivity in agriculture. Drought stress reduces the yield by affecting the key plant metabolic pathways. The capability of plants to switch on or off a series of genes result in alterations of the physiological and morphological attributes, thereby allowing plants to escape, tolerate or avoid drought stress. Different genes, transcription factors and signal transduction pathways are induced by drought stress. Advances in genome editing technologies have revolutionized the agriculture sector by using more accurate genome engineering techniques for targeted crop traits. Clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) technology is a robust and efficient approach for developing plant/crop varieties tolerant to different climatic changes. The use of new genome editing technologies like CRISPR facilitates the creation of plant species with improved drought tolerance. Thus this review aims to elucidate the basic plant responses to stress and the mechanisms for the adaptation and attainment of tolerance.